IN SILICO DOCKING STUDIES ON THE ANTI-CANCER EFFECT OF THYMOQUINONE ON INTERACTION WITH PTEN- A REGULATOR OF PI3K/ AKT PATHWAY - Nithya, Gajendran; Sakthisekaran, Dhanapal (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The statistics on cancer imposes the urge to extend new methods to control this deadly form of the disease. Phosphatase and tensin homolog located on chromosome 10q23 (PTEN) is inactivated in a subset and AKT is frequently activated in cancer. The PTEN is the central negative regulator of the phosphatidylinositol 3-kinase (PI3K)/AKT signaling cascade that influences multiple cellular functions including cell growth, survival, proliferation and migration in a context-dependent manner. Dysregulation of this signaling pathway contributes to different types of cancers. The objective of the study is to explore the anti-cancer potential of thymoquinone (TQ) by analyzing the interaction between TQ with the target protein PTEN. Methods: The three dimensional structure of TQ is designed using in-silico methods, and the structure of PTEN is obtained from National Center for Biotechnology Information against protein data bank. The query sequence from 8 to 353 amino acids was found to be 85% homologous to ID5R. For the target protein PTEN with 403 residues, protein families analysis covered the important domains in PTEN. Result: TQ showed the binding energy of âˆ’7.37 Kcal/mol against PTEN with three hydrogen bonds. Conclusion: Present study suggests that TQ might inhibit abnormal cell proliferation occurring in cancer by modulating the activity of PTEN, a negative regulator of PI3K/AKT pathway. Keywords: Cancer, Thymoquinone, Phosphatase and tensin homolog located on chromosome 10q23, Docking and hydrogen bonds. Â 